ISSUES OF SOCIAL TAX AND ITS DIGITALIZATION IN A MARKET ECONOMY - Turayev Alijon Akmal o‘g‘li; Turdiboev Diyorbek Ravshanbek o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Our article is devoted to the study of social tax in the context of a market economy and its digitalization. We consider issues related to social tax as an instrument for the financial sustainability of the state and ensuring social justice. We pay special attention to digital technologies and their role in the modern system of collection and administration of social taxes.